(untitled) (Journal of the College of Education for Women, 2019)
This study aimed to investigate the relationship between narcissisticpersonality and altruistic behavior for a subject of (307) gifted high schoolsstudents, including (139)male and (168) female students ,both the scale ofnarcissistic personality and the scale of altruistic behavior (Hameed ,2002) werechecked for its validity and reliability ,and both the level of narcissism and thelevel of altruism for the students were measured in compare to the medium averageand approved to be statistically significant at (0.05) level.Results showed that there were no significant differences in the altruisticbehavior between males and females ,results showed significant differences innarcissism levels between males and females for the favor of the males ,finally theresults also showed that there was no significant relationship between narcissismand altruistic behavior .